Indentation Hardness and Elastic Recovery of Some Hardwood Species - Maciej Sydor; Grzegorz Pinkowski; Martin Kučerka; Richard Kminiak; Petar Antov; Tomasz Rogoziński (Applied Sciences, 2022)
The purpose of the study was to measure the Brinell hardness (HB) of six wood species and evaluate the ability to recover the depth of the imprint (self-re-deformation). Straight-grain clear samples of ash, beech, alder, birch, iroko, and linden wood were prepared. Measurements were made in the three main reference timber cross-sections: radial (R), tangential (T), and axial/longitudinal (L) and with two measuring loads of 30 kG and 100 kG (294.2 N and 980.7 N). The tested wood species could be classified into hard (ash, beech), medium-hard (alder, birch, iroko), and soft (linden) wood species. The HBs of each tested wood species differed in the cross-sections, i.e., side hardness (R, T) and end hardness (L). Higher HB values were obtained at 100 kG load in all species and all three cross-sections. The lowest influence of the measurement force value on the HB value was revealed for the soft wood species (linden: 107–118%). This influence was visible for the other five medium-hard and hard wood species, ranging from 125% to 176%. The percentage of temporary imprint in total imprint depth (x/H) varied from 12 to 33% (linden 12–18%—the lowest self-re-deformation ability; beech 25–33%—the highest self-re-deformation ability). The results of this study underline that the higher the density of the wood, the higher the Brinell hardness, and, simultaneously, the greater the measurement force used, the higher the Brinell hardness measured. The ability of self-re-deformation in wood’s R and T cross-sections depends on the wood density and the measuring force used. In contrast, this ability only depends on the wood density in the L cross-section. Those observations imply that the compaction of the cell structure during side compression is mainly non-destructive, while the longitudinal deformation of the cell structure (the buckling of cell walls and fracture of ends of the cells) is to a great degree destructive and irreversible. These results can be used in the construction and furniture sectors, especially when designing products and planning the woodworking of highly loaded wood floors and furniture elements.